2016
DOI: 10.1186/s13098-016-0194-9
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of intestinal tissue 3-deoxyglucosone attenuated GLP-1 secretion and its insulinotropic effect in rats

Abstract: BackgroundOur recent findings support the idea that 3-deoxyglucosone (3DG), a dietary composition, has been suggested as an independent factor for the development of prediabetes. Secretion of glucagon-like peptide-1 (GLP-1) has been suggested to be impaired in T2DM and in conditions associated with hyperglycemia. Since low oral bioavailability of 3DG has been indicated in a single administration study, in the present study we examined if 3DG is capable of accumulating in intestinal tissue of rats after 2-week … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…During early pregnancy, the activity of the pancreatic beta cells is increased, as evidenced by the enhanced insulinotropic effect of glucose observed in both women and rats, while whole-body insulin sensitivity is unchanged or even augmented [42]. Consequently, it has been proposed that hyperinsulinemia in the first 2 trimesters of gestation is the principal factor promoting maternal lipogenesis and fat deposition.…”
Section: Contribution Of Hormones To the Metabolic Adaptations Duringmentioning
confidence: 99%
“…During early pregnancy, the activity of the pancreatic beta cells is increased, as evidenced by the enhanced insulinotropic effect of glucose observed in both women and rats, while whole-body insulin sensitivity is unchanged or even augmented [42]. Consequently, it has been proposed that hyperinsulinemia in the first 2 trimesters of gestation is the principal factor promoting maternal lipogenesis and fat deposition.…”
Section: Contribution Of Hormones To the Metabolic Adaptations Duringmentioning
confidence: 99%
“…Previous studies by us and others have revealed that 3DG exhibits poor absorbing characteristics (Kato et al 1990, Degen et al 2014, Zhang et al 2016), suggesting the harmful action of 3DG on the function of L-cells of the gastrointestinal tract. Indeed, we previously reported that acute administration of 3DG by gastric gavage induced the impairment in oral glucose-stimulated GLP-1 secretion in rats.…”
Section: Discussionmentioning
confidence: 92%
“…Studies in diabetic patients have suggested that 3DG is associated with diabetes (Niwa 1999, Kusunoki et al 2003. Our previous studies in clinical and animal research have indicated 3DG as an independent factor for the development of prediabetes (Jiang et al 2012, Liang et al 2016a, Zhang et al 2016, Wang et al 2017. Acute and two-week 3DG administration by gastric gavage induced acute glucose intolerance and glucose homeostatic dysregulation in rats, respectively.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations